Alteration of IGF-1 bioavailability due to PAPPA2 deficiency leads to sex-specific metabolic disturbances - López-Gambero, Antonio J.; Vargas, Antonio; Fernández-Arjona, María del Mar; Rubio-Lamia, Leticia Olga; De Ceglia, Marialuisa; Vera-Fernández, Carlos; Campillo-Calatayud, Ana; Rivera-González, Patricia; Rodriguez-de-Fonseca, Fernando; Barrios, Vicente; Chowen, Julie A.; Argente, Jesús; et al. (ELSEVIER, 2025)
Background: The growth hormone (GH)/insulin-like growth factor (IGF-1) axis determines optimal growth and affects metabolism and energy homeostasis. Pregnancy-associated plasma protein-A2 (PAPPA2) regulates bioactive IGF-1 availability and patients with PAPPA2 deficiency have impaired growth and glucose metabolism. This axis is altered in metabolic disturbances such as obesity and anorexia nervosa in a sex-specific manner, but the mechanisms involved are not completely understood. Here we evaluated how Pappa2 deficiency affects energy homeostasis, focusing on male and female differences. Methods: Growth and energy homeostasis were determined in male and female Pappa2ko/ko mice and control Pappa2wt/wt littermates, as well as their response to recombinant human (rh)PAPPA2, rhIGF-1 and rhIBFBP5. Effects of a high-carbohydrate diet (HCHD) on glucose tolerance, fuel partitioning, de novo lipogenesis and energy homeostasis were determined. Results: Pappa2ko/ko mice had reduced body weight, bone length and lipid deposition associated with higher energy expenditure and intake. Male Pappa2ko/ko mice had mild glucose intolerance, altered bone mineral properties and higher energy costs for locomotor activity possibly due to inefficient muscle mitochondrial activity; whereas female Pappa2ko/ko mice had enhanced fatty acid oxidation on a normal diet, but not on a HCHD. All Pappa2ko/ko mice had lower hepatic fat deposition associated with lower IGF-1 activity in the liver, while fatty acid metabolism dysregulation in adipose tissue was found only in females. Conclusion: These data reinforce the importance of the GH/IGF-1 axis in metabolic control and emphasize the relevance of its fine-tuned control by Pappa2. Moreover, the differences between sexes in metabolic imbalances underscore the relevance of sex-specific strategies for treatment of metabolic imbalances.
Keywords: Endocrinología; Metabolismo - Aspectos endocrinos; Hormonas; Diferencias sexuales; Homeostasis; IGF-1; PAPPA2; Energy homeostasis; Sex differences